THE DYNAMICS OF CHILD'S ORAL MICROBIOTA: A REVIEW - Hafsan, Hafsan; Nur, Fatmawati; Mustami, Muh. Khalifah (JURNAL SIPAKALEBBI, 2023)
The oral microbiota in children changes with growth and development. The composition of the microbiota is influenced by genetic factors, oral environment, diet, and oral hygiene habits. Changes in oral microbiota composition have significant health implications in children, that is can contribute to the development of dental diseases, such as dental caries and periodontal disease. In addition, oral microbiota also plays an important role in the development of the child's immune system, therefore it is very important to understand the dynamics of child's oral microbiota. The method used in writing this scientific article is the literature review method. Various studies on oral microbiota in children show that in early life, oral microbiota is dominated by bacteria such as Streptococcus, Prevotella, and Veillonella. Along with the introduction of solid foods and the development of teeth, the composition of oral microbiota will change and become more diverse. Genetic factors can influence a child's susceptibility to the growth of pathogenic bacteria, while the oral environment, diet, and oral hygiene habits play an important role in the diversity and balance of oral microbiota. A balanced composition of microbiota plays a role in preventing dental diseases and maintaining overall oral health. Maintaining oral hygiene and adopting a healthy diet are important factors in maintaining the health of a child's oral microbiota. In addition, an understanding of the relationship between oral microbiota and a child's immune system is also an important factor in maintaining overall health.